2017
DOI: 10.23922/jarc.2017-022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bleeding in patients receiving fondaparinux after colorectal cancer surgery

Abstract: Abstract:Objective: The aim of this study was to identify risk factors for bleeding complications in patients who receive Venous thromboembolism (VTE) prophylaxis with fondaparinux (FPX) after colorectal cancer surgery. Methods: Records of 546 patients who underwent VTE prophylaxis with intermittent pneumatic compression and FPX after colorectal cancer surgery between January 2009 and May 2014 were reviewed. Patient characteristics, surgical procedures, and patient laboratory data were examined to identify ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(11 reference statements)
0
3
1
Order By: Relevance
“…These changes can lead to several postoperative complications, such as VTE and bleeding. It has been reported that VTE and bleeding at or greater than CD grade III after curative resection of primary colorectal cancer occurs at rates of 0 to 0.16% and 0.2 to 0.81%, respectively [22][23][24]. Compared with these data, in the present study, VTE and bleeding events more frequently occurred (Table 4).…”
Section: Discussioncontrasting
confidence: 44%
“…These changes can lead to several postoperative complications, such as VTE and bleeding. It has been reported that VTE and bleeding at or greater than CD grade III after curative resection of primary colorectal cancer occurs at rates of 0 to 0.16% and 0.2 to 0.81%, respectively [22][23][24]. Compared with these data, in the present study, VTE and bleeding events more frequently occurred (Table 4).…”
Section: Discussioncontrasting
confidence: 44%
“…Rectal cancer surgery is frequently associated with complications [15][16][17]. Defecation disorders are among the most frequent complications after rectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These changes can lead to several postoperative complications, such as VTE and bleeding. It has been reported that VTE and bleeding at or greater than CD grade III after curative resection of primary colorectal cancer occurs at rates of 0 to 0.16% and 0.2 to 0.81%, respectively [ 22 24 ]. Compared with these data, in the present study, VTE and bleeding events more frequently occurred (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%